Comparative evaluation of effect of microcurrent electrical stimulation on acupoints to control gag reflex in patients receiving prosthodontic treatment: An in vivo study - Shanvi Agrawal; Seema Sathe Kambala; Anjali Bhoyar Borle; Tanvi Balwani (Wolters Kluwer Medknow Publications, 2022)
Aims: The aim of this study is to see if microcurrent electrical stimulation on two acupoints, auricular and Hegus, can help patients prevent their gag reflex. Settings and Design: This was an in vivo cross-sectional study. Materials and Methods: Thirty patients were randomly assigned to three groups: A, B, or C, of ten patients present in each group. Group A and Group B undergone electroacupuncture (microcurrent electrical stimulation) using electroacupuncture device on auricular point and Hegus point (Li 4), respectively, for 1 min and Group C formed the placebo group, point Shou San Li (Li 10). The gag severity index and the gag prevention index were used to measure the gag reflex, which was done in two steps. Statistical Analysis Used: SPSS (SPSS Inc., Chicago IL, USA) version 24 software was used for statistical analysis. Paired t-test, one-way analysis of variance test, post hoc Bonferroni test was used to analyse and compare the data. Results: It was found that Point A and Point B were significantly effective in reducing the severity of gag reflex. Point C demonstrated insignificant results. In addition, Point B (Hegus [Li4]) is more effective than Point A (auricular) in controlling the gag reflex in patients within the set age group of 20-70 years of age. Conclusions: Microcurrent electrical stimulation is a useful adjuvant in the treatment of unfavorable gag reflexes during routine dental procedures. Point Hegus and point auricular acupuncture are both useful in decreasing the severity of gag reflex, with point Hegus being more effective than point auricular.